Advanced Bio-Based PVA Composite Films Reinforced with Bacterial Cellulose and Graphene Oxide: Enhanced Mechanical, Thermal, Flame-Retardant, and UV-Blocking Properties - Nguyen, Tuan Anh; Nguyen, Van Hoan (Trends in Sciences, 2025)
This research elucidates the formulation and characterization of an eco-friendly bio-composite film made with polyvinyl alcohol (PVA), bacterial cellulose (BC), and graphene oxide (GO). The optimized composition, incorporating 3 wt.% BC and 0.5 wt.% GO, yielded substantial improvements in mechanical properties, achieving a 47% increase in tensile strength and a 65% enhancement in impact resistance compared to pure PVA, while preserving desirable flexibility. Microstructural and spectroscopic analyses-including scanning electron microscopy (SEM), Fourier-transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD)-confirmed homogeneous dispersion and strong interfacial compatibility among components. The addition of GO significantly enhanced flame retardancy, raising the limiting oxygen index (LOI) to 27.8% and enabling the film to attain UL-94 V-1 classification. Thermogravimetric analysis revealed improved thermal stability, while UV-visible spectroscopy demonstrated a UV-blocking efficiency of 95.3% at 280 nm. These findings underscore the synergistic reinforcing effect of BC and GO in enhancing the mechanical strength, thermal resistance, flame retardancy, and UV-shielding capacity of the bio-composite film made with PVA, BC and GO, highlighting its promising potential for sustainable applications in packaging, biomedical materials, and protective coatings. HIGHLIGHTS A novel eco-friendly bio-composite film based on PVA, bacterial cellulose (3 wt.%), and graphene oxide (0.5 wt.%) was successfully developed. The composite showed significant mechanical improvements: tensile strength increased by 47% and impact resistance by 65% compared to pure PVA. Flame retardancy was enhanced with a limiting oxygen index (LOI) of 27.8% and UL-94 V-1 classification. The film achieved 95.3% UV-blocking efficiency at 280 nm and demonstrated improved thermal stability. Synergistic reinforcement between bacterial cellulose and graphene oxide led to enhanced interfacial compatibility and multifunctional performance, making the composite suitable for sustainable packaging and biomedical applications. GRAPHICAL ABSTRACT